1997
DOI: 10.1074/jbc.272.16.10811
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Peroxisome Proliferator-activated Receptor γ Activity by Mitogen-activated Protein Kinase

Abstract: Adipocyte differentiation is regulated both positively and negatively by external growth factors such as insulin, platelet-derived growth factor (PDGF), and epidermal growth factor (EGF). A key component of the adipocyte differentiation process is PPAR␥, peroxisomal proliferator-activated receptor ␥. To determine the relationship between PPAR␥ activation and growth factor stimulation in adipogenesis, we investigated the effects of PDGF and EGF on PPAR␥1 activity. PDGF treatment decreased ligand-activated PPAR␥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
279
1
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(308 citation statements)
references
References 36 publications
19
279
1
9
Order By: Relevance
“…The addition of exogenous 13-(S)-HODE, at lower concentrations than used to observe binding to PPAR␥, up-regulates both the EGF-and serum-dependent MAPK pathway and subsequently PPAR␥ phosphorylation. The addition of a MEK inhibitor results in the inhibition of MAPK activity and subsequently PPAR␥ phosphorylation, which supports the conclusion that PPAR␥ phosphorylation is mediated by MAPK as reported in fat cells (29). This phenomenon is specific for linoleic acid metabolites as 13-(S)-HODE, 13-(R)-HODE, and 13-(S)-HpODE all have the same effect, while 15-(S)-HETE, an arachidonic acid metabolite, was inactive and in fact appeared to inhibit phosphorylation.…”
Section: Discussionsupporting
confidence: 69%
“…The addition of exogenous 13-(S)-HODE, at lower concentrations than used to observe binding to PPAR␥, up-regulates both the EGF-and serum-dependent MAPK pathway and subsequently PPAR␥ phosphorylation. The addition of a MEK inhibitor results in the inhibition of MAPK activity and subsequently PPAR␥ phosphorylation, which supports the conclusion that PPAR␥ phosphorylation is mediated by MAPK as reported in fat cells (29). This phenomenon is specific for linoleic acid metabolites as 13-(S)-HODE, 13-(R)-HODE, and 13-(S)-HpODE all have the same effect, while 15-(S)-HETE, an arachidonic acid metabolite, was inactive and in fact appeared to inhibit phosphorylation.…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that phosphorylation of Ser-112, adjacent to the sumoylation site, as revealed by this work, on PPAR␥ by mitogen-activated protein kinase significantly inhibited both ligand-independent and ligand-dependent transcriptional activation by PPAR␥ (15). Mutation analysis of the phosphorylation site revealed that this phosphorylation-mediated transcriptional repression was not due to a reduced capacity to make PPAR␥⅐RXR␣ complexes or the impairment of recognition of its DNA binding site (14). An AF-1 domain of PPAR␥ may be negatively regulated by phosphorylation and sumoylation.…”
Section: Discussionmentioning
confidence: 80%
“…PPARg can also be SUMOylated in a ligand-dependent manner in the LBD at Lys-365 (Pascual et al 2005). Another regulatory covalent modification of PPARg is phosphorylation at Ser-112 by mitogen-activated protein kinases (MAPKs) such as p44/p42 (ERKs 1 and 2) and c-Jun amino-terminal kinase (JNK), which results in transcriptional inactivation of PPARg (Camp and Tafuri 1997). Although it is widely accepted that phosphorylation of PPARg2 inhibits its activity, a point mutation at Ser-112 does not disrupt the ability of PPARg2 to confer adipogenesis (Rangwala et al 2003).…”
Section: Ppargmentioning
confidence: 99%